2021
DOI: 10.1186/s12884-021-03956-6
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and pregnancy outcomes of pregnant women exposed to second-line anti-tuberculosis drugs in South Africa

Abstract: Background Multi-drug resistant and rifampicin-resistant tuberculosis (MDR/RR-TB) in pregnant women is a cause for concern globally; few data have described the safety of second-line anti-TB medications during pregnancy. We aim to describe TB treatment and pregnancy outcomes among pregnant women receiving second-line anti-tuberculosis treatment for MDR/RR-TB in Johannesburg, South Africa. Methods We conducted a retrospective record review of pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 15 publications
0
20
0
1
Order By: Relevance
“…Similarly, another study found 91% (10/11) of preterm labour were among those with TB-HIV coinfection compared with those with TB only. 42 One study found no statistical significance in association between TB-HIV coinfection and maternal or fetal outcome. 62 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, another study found 91% (10/11) of preterm labour were among those with TB-HIV coinfection compared with those with TB only. 42 One study found no statistical significance in association between TB-HIV coinfection and maternal or fetal outcome. 62 …”
Section: Resultsmentioning
confidence: 99%
“… 22 26 27 44 45 TB outcomes for newborns with congenital TB include: resolution or improvement of TB at follow-up, loss to follow-up, died without TB treatment or unknown. 22 26 28 40 44–46 Other reported poor fetal outcomes included stillbirth (case reports n=1, case series n=2, cohort studies n=3), 30 47 48 spontaneous abortions/fetal demise (case reports n=3, case series n=6, cohort study n=1) 19 29 49–55 or induced abortions (case reports n=4, series n=1, cohort study n=2, other n=1) 42 49 55–60 and fetal growth restriction/retardation (case series n=1, case-control n=1). 41 61 One case series reported stillbirth, spontaneous abortions/fetal demise and induced abortions, 49 and one cohort study reported spontaneous and induced abortions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our electronic database searches identified 487 records. After removal of duplicates, excluding studies by title and abstract screening and full-text review (eTable 5 in the Supplement ), 10 studies 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 were included in the meta-analysis, which included 288 pregnant patients with MDR-TB ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The studies were conducted in 5 different countries, and the data were collected from 1996 to 2019 (eTable 6 in the Supplement ). Among the included studies, 9 were published in English, 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 and 1 was in Spanish. 23 Treatment outcomes were reported for all 10 studies, which included 275 of the 288 pregnant patients with MDR-TB ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%